HUBUNGAN KEIKUTSERTAAN IBU HAMIL DALAM MENGIKUTI KELAS IBU HAMIL DENGAN PERSIAPAN MENGHADAPI PERSALINAN DI WILAYAH KERJA PUSKESMAS KARANGANOM KLATEN - Astri Wahyuningsih; Piscolia Dynamurti Wintoro (INVOLUSI: Jurnal Ilmu Kebidanan, 2019)
The MMR ratio in developing countries reaches 450 mothers per 100,000 live births. The government implements a class program for pregnant women to reduce maternal mortality. In 2011, only 2,508 classes of pregnant women were formed throughout the archipelago. The condition of the class of pregnant women at this time, there has been no significant increase in this number, and the majority of the existing classes of pregnant women have not been able to run well, many obstacles are faced, both from pregnant women themselves. This can affect the readiness of the mother to face childbirth. This study aims to determine the relationship between the participation of pregnant women in attending classes for pregnant women with preparation for childbirth in the working area of ​​Puskesmas Karanganom Klaten. This research method is observational with cross sectional approach design. The number of research samples was 35 respondents. Sampling was using purposive sampling technique. The instrument used was a questionnaire. The data were analyzed using the chi square test. The results showed that the participation of pregnant women in participating in the class program for pregnant women was mostly passed as many as 71.4% of respondents, some were ready to face labor as many as 62.9% of respondents and p value 0.011 (p <0.05). The conclusion of this study is that there is a relationship between the participation of pregnant women in attending classes for pregnant women with preparation for childbirth in the working area of ​​Puskesmas Karanganom Klaten. Suggestions for mothers to take part in the implementation of classes for pregnant women which are held in the village regularly.